Reporting Bias is Highly Prevalent in Systematic Reviews and Meta-analyses of Platelet Rich Plasma Injections for Hip Osteoarthritis - Daniel Kim, M.D; Bryan S. Bashrum, B.S; Jacob L. Kotlier, B.A; Cory K. Mayfield, M.D; Ashley A. Thompson, B.S; Maya Abu-Zahra, B.A; Mina Hwang, B.S; Ioanna K. Bolia, M.D; Frank A. Petrigliano, M.D; Joseph N. Liu, M.D (Elsevier, 2024)
Purpose: To describe the incidence and types of spin in systematic reviews of platelet-rich plasma (PRP) injections for hip osteoarthritis (OA) and to determine whether patterns in study characteristics could be identified among studies with identifiable spin. Methods: The PubMed, Scopus, and SPORTDiscus databases were queried. Inclusion criteria were systematic reviews or meta-analyses that included an assessment of intra-articular PRP injections as a stand-alone treatment for hip OA. Two authors independently assessed the presence of spin in the included studies and recorded general study characteristics. The prevalence of the 15 different categories of spin was quantified using descriptive statistics. Results: Fifteen studies met inclusion criteria for this study. All studies contained at least two types of spin (range 2-9), with a median of 2. The most common type of spin was type 14 ("Failure to report a wide confidence interval of estimates"), which was observed in 10 studies. The second most common type of spin was type 13 ("Failure to specify the direction of the effect when it favors the control intervention"), found in 6 studies. Conclusions: Spin is highly prevalent in abstracts of systematic reviews of PRP in the treatment of hip OA. Several associations were found between spin types and the study characteristics of AMSTAR 2 rating, Scopus CiteScore, journal impact factor, and PROSPERO preregistration. When present, spin in the abstracts of reviewed studies tended to favor the use of PRP in hip osteoarthritis. Clinical Relevance: It is important to understand the prevalence of spin in published abstracts, especially in areas of great impact or interest, so authors and readers can have a greater awareness of this potential form of bias.